A Hidden Chemical Assembly Mechanism: Reconstruction‐by‐Reconstruction Cycle Growth in HKUST‐1 MOF Layer Synthesis - Koehler, T.; Schmeink, J.; Schleberger, M.; Marlow, F. (Chemphyschem, 2025)
Thin metal‐organic framework films grown in a layer‐by‐layer manner have been the subject of growing interest. Herein we investigate one of the most popular frameworks, the type HKUST‐1. Firstly, we show a special synthesis procedure resulting in quick but optically perfect growth. This enables the synthesis of films of excellent optical quality within a short timeframe. Secondly and most importantly, we address the known, but not fully understood observation that the expected growth rate of one monolayer per cycle is strongly exceeded, e. g. by a factor of 4. This is an often‐ignored inconsistency in the literature. We offer a growth model using a reconstruction process in every cycle leading to a deterministic reconstruction‐by‐reconstruction (RbR) cycle growth with a 4‐times higher growth rate. It represents an up‐to‐now hidden chemical assembly mechanism. The metal‐organic framework HKUST‐1 grown in a step‐wise manner shows growth rates in clear disagreement with the usual layer‐by‐layer (LbL) model. A nearly exact 4‐times higher rate compared to the simple growth model is found and a modified model involving lattice reconstruction is proposed.